2005
DOI: 10.1016/j.cub.2005.05.052
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear and Division-Plane Positioning Revealed by Optical Micromanipulation

Abstract: The position of the division plane affects cell shape and size, as well as tissue organization. Cells of the fission yeast Schizosaccharomyces pombe have a centrally placed nucleus and divide by fission at the cell center. Microtubules (MTs) are required for the central position of the nucleus. Genetic studies lead to the hypothesis that the position of the nucleus may determine the position of the division plane. Alternatively, the division plane may be positioned by the spindle or by morphogen gradients or r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 29 publications
1
65
0
Order By: Relevance
“…It has been shown that the nucleus dynamically influences Mid1 and the cell division site positioning in fission yeast. 35,36 In kin1Δ cells, CAR formation 25 and septum synthesis 22 are only affected in their localization and Mid1 is properly localized around the nucleus (unpublished observations) as in Kin1 OFF cells (Suppl. Fig.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…It has been shown that the nucleus dynamically influences Mid1 and the cell division site positioning in fission yeast. 35,36 In kin1Δ cells, CAR formation 25 and septum synthesis 22 are only affected in their localization and Mid1 is properly localized around the nucleus (unpublished observations) as in Kin1 OFF cells (Suppl. Fig.…”
Section: Discussionmentioning
confidence: 82%
“…Since position of the CAR and the subsequent septum is specified in late G 2 and early mitosis by the position of the nucleus, [35][36][37] we monitored the position of the nucleus relative to the cell ends in late G 2 cells (≥10 μm) and we observed that a higher proportion of nuclei were misplaced towards the new cell end (according to the birthscar) in the Kin1 OFF (28 ± 1.1% with a short/long ratio <0.85, n = 206) compared to the Kin1 ON condition (16.4 ± 1.8%, n = 186). However, nuclear dynamics of interphase nuclei were not significantly different between Kin1 ON (Suppl.…”
Section: Resultsmentioning
confidence: 99%
“…4,5 In budding yeast, the position of the division plane is defined by the neck between the mother cell and the bud, whereas in fission yeast it is defined by the position of the interphase nucleus. 6,7 Cytoplasmic microtubules play an essential role in yeast nuclear positioning by both providing a link between the nucleus and the cell cortex, and by acting as the necessary purveyors of pushing and pulling forces. 8 Moreover, the regulation of microtubule dynamics, attachment and localization is crucial for the ability to generate asymmetric forces that orient and move the nucleus.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, this hypothesis was first formulated from the analysis of microtubule defective mutants displaying delocalized nuclei and septa [Toda et al, 1983;Radcliffe et al, 1998]. More recent studies, in the same spirit as the spindle displacement experiments developed by Ray Rappaport in marine eggs [Rappaport, 1985], have shown that displacing the nucleus from the cell middle by cell centrifugation in the absence of microtubules, or using optical tweezers, indeed results in the delocalization of contractile rings and septa to the new position occupied by the nucleus [Daga and Chang, 2005;Tolic-Norrelykke et al, 2005; see Fig. 2].…”
mentioning
confidence: 99%